Air Warming of Motor Vehicles - Elenskii,G. (1973)
The report describes an inexpensive vehicle heating system devised for vehicles parked in open spaces in Arctic regions. Trans. of Nauchno-Tekhnicheskie Obshchestva SSSR, n9 p8-10 1971.